2012
DOI: 10.1021/tx300194t
|View full text |Cite
|
Sign up to set email alerts
|

Immunotoxicity Induced by Acute Subtoxic Doses of Paraquat Herbicide: Implication of Shifting Cytokine Gene Expression toward T-Helper (TH)-17 Phenotype

Abstract: Paraquat (PQ) is a free radical-inducing agent commonly used as an herbicide. This study assesses the acute immunotoxicity of PQ in BALB/c mice and examines its effect on cytokine gene expression profile. It was found that single subtoxic oral doses of 2, 4, and 20 mg/kg significantly inhibited the in vitro mitogen-induced proliferation in both T and B cells. Also, such acute doses have resulted in significant reduction of the IgM plaque-forming cells counts. The impact of PQ on the cytokine gene expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Tissue injury is mainly due to reactive oxygen species (ROS) causing irreversible oxidative damage to molecular structures, cell functions and exacerbated immune response (Wu et al, 2018). Recent studies have shown that PQ directly impacts on immunity and immune cell activities (Hassuneh et al 2012;Riahi et al 2010) with effects such as decreased interferon (IFN)-γ production and phagocytic activity of monocytes in mice (Riahi et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Tissue injury is mainly due to reactive oxygen species (ROS) causing irreversible oxidative damage to molecular structures, cell functions and exacerbated immune response (Wu et al, 2018). Recent studies have shown that PQ directly impacts on immunity and immune cell activities (Hassuneh et al 2012;Riahi et al 2010) with effects such as decreased interferon (IFN)-γ production and phagocytic activity of monocytes in mice (Riahi et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, at this point it is difficult to distinguish if its proinflammatory activity is due to the GR antagonism or ROS formation. Nevertheless, it is clear that PRQ has ability to affect immune system, which was demonstrated in vivo in BALB/C mice, where single subtoxic oral doses (2, 4, and 20 mg/ kg) inhibited proliferation of T-and B-cells (Hassuneh et al, 2012). The results of this study also suggested that PRQ at higher concentrations can deplete immune functions, but it can alter immune responses towards the proinflammatory profiles at lower concentrations.…”
Section: Discussionmentioning
confidence: 50%
“…One recent in vivo study with mice exposed acutely to paraquat (Hassuneh et al 2012), which included in vitro exposure of mouse splenocytes, found evidence of a negative dose response (more marked response at lower concentrations) in vivo and in vitro. It is unclear if this finding in a single study is reflective of a more general phenomenon.…”
Section: Studies On Individual Chemicals: 9 Papers In Appendix Ymentioning
confidence: 99%